Aetiological Factors of Osteoarthritis: A Review Update (Journal of Current and Advance Medical Research, 2015)
Osteoarthritis (OA) is no longer considered degenerative or wear and tear arthritis; rather involves dynamic biomechanical, biochemical and cellular process. Indeed, the joint damage that occurs in OA is the result of active remodeling involving all the joint structures. Although articular cartilage is at the center of change, OA is viewed as a disease of the entire joint. Traditionally, OA has been viewed as an inevitable degenerative condition of the cartilage. It is currently viewed as a biomechanical and biochemical inflammatory disease of the entire joints. Osteoarthritis (OA) is the most common type of arthritis. Its high prevalence, especially in the elderly, and the high rate of disability related to disease make it a leading cause of disability in the elderly. Because of the aging of Western populations and because obesity, a major risk factor, are increasing in prevalence, the occurrence of osteoarthritis is on the rise. In the United States, osteoarthritis prevalence will increase from 66100% by the year 2020. OA affects certain joints, yet spares others. Commonly affected joints include the cervical and lumbosacral spine, hip, knee, and first metatarsal phalangeal joint (MTP). In the hands, the distal and proximal inter-phalangeal joints and the base of the thumb are often affected. Usually spared are the wrist, elbow, and ankle.Journal of Current and Advance Medical Research 2015;2(1):18-23DOI: http://dx.doi.org/10.3329/jcamr.v2i1.22584